Análise e modelagem da síntese enzimática de galacto-oligossacarídeos - Schultz, Guilhermina (2016)
Galactooligosaccharides are indigestible oligosaccharides with recognized prebiotic capacity. They can be synthesized enzymatically from lactose-rich substrates using the β-galactosidase enzyme by means of a kinetically controlled reaction in which they are intermediates (synthesis) in the hydrolysis reaction. The predominance of synthesis on the hydrolysis depends mainly on the concentration of lactose and origin of β-galactosidase, but it also depends on other factors, such as temperature, pH, ionic strength and water activity. Apart from pure lactose, other substrates with high concentration of lactose may be used, such as whey and whey permeate. The objective of this research was to study the enzymatic production of galactooligosaccharides (GOS) from lactose and whey permeate using free β-galactosidase from Kluyveromyces lactis to reach mathematical models that enable the use computational tools for process optimization. A rotational central composite design to verify the influence of pH, temperature and ionic strength in the initial rates of hydrolysis and synthesis, selectivity and total enzyme activity was used. Lactose (pure or present in whey permeate) were used as substrate (220 g/L) and the reactions were conducted in a potassium phosphate buffer (various concentrations) in the presence of cofactors (10 mM NaCl, and 1.5 mM MgCl2). The results showed that, within the studied region, both rates, of synthesis and hydrolysis using lactose or permeate, increase with temperature increase and pH decreases. Selectivity is maximized by increasing pH. Stability analysis of β-galactosidase Kluyveromyces lactis was also addressed. These tests were performed in presence of cofactor, incubating the enzyme in potassium phosphate buffer. The temperature was varied from 35 to 45 ° C (pH 7 and 50 mM), pH 6 to 8 (35 ° C and 50 mM) and ionic strength 25 to 200 mM (35 ° C and pH 7) and samples were collected over time. Among tested models, what best fits the experimental data is the reversible inactive intermediate model. However, this model could not predict behaviors such as those obtained when using 25, 100 and 200 mM. Fitting of kinetic models for GOS synthesis were made by nonlinear regression. Experimental data of different GOS synthesis assays employing lactose and whey permeate as substrates was used. The results showed that a simple model (which does not take into account the formation of galactobiose) does not fit the experimental data. Recent model proposed in the literature that takes into account such training, fits the data, but it has a problem of phenomenological inconsistency. The model proposed in this work fit the experimental data and does not show inconsistencies in the balance of glucose residues per galactose. Moreover, the model allows the estimation of GOS fraction formed only by galactose, which allows to discriminate disaccharides into galactobiose (having prebiotic properties) and lactose.